Исследования некрополей Сугдеи в 2007—2009 гг. - Майко, В.В.; Джанов, А.В.; Фарбей, А.М. (Археологічні дослідження в Україні, 2010)
Published are results of excavations at four city necropolei of various dates situated on the territory of north-eastern (Sudak IX) and central (St. Paraskeva church, a temple of 1994) parts of posad, as well as on the territory of citadel. Burials at the area of Sudak IX necropolis cover the structures of the 8th—10th centuries and the middle of the 14th c.